Determination of due standards of special readiness and their influence on effectiveness of individual technical and tactical actions of athletes in game sports - Rodin, A. V.; Zakharov, P. S.; Artyugin, A. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
These diagnostics of special readiness and pedagogical observation of competitive process of the qualified athletes specializing in basketball and volleyball are presented in article. Results of researches reveal features of work of a respiratory system and effectiveness of individual technical and tactical actions in the course of the control games which gave the chance to define due standards of special readiness of players in the competitive period of a year training cycle.